Hyperprogressive disease in early‐phase immunotherapy trials: Clinical predictors and association with immune‐related toxicities. Issue 8 (15th February 2019) - Kanjanapan, Yada; Day, Daphne; Wang, Lisa; Al‐Sawaihey, Hamad; Abbas, Engy; Namini, Amirali; Siu, Lillian L.; Hansen, Aaron; Razak, Albiruni Abdul; Spreafico, Anna; Leighl, Natasha; Joshua, Anthony M.; et al.
Abstract : Background: A subset of patients treated with immune checkpoint inhibitors experience an accelerated tumor growth rate (TGR) in comparison with pretreatment kinetics; this is known as hyperprogression. This study assessed the relation between hyperprogressive disease (HPD) and treatment‐related toxicity and clinical factors. Methods: This study reviewed patients with solid tumors who were enrolled in early‐phase immunotherapy trials at Princess Margaret Cancer Centre between August 2012 and September 2016 and had computed tomography scans in the pre‐immunotherapy (reference) and on‐immunotherapy (experimental) periods. HPD was defined as progression according to Response Evaluation Criteria in Solid Tumors 1.1 at the first on‐treatment scan and a ≥2‐fold increase in TGR between the reference and experimental periods. Treatment‐related toxicities requiring systemic therapy, drug delays, or discontinuation were considered clinically significant adverse events (CSAEs). Results: Of 352 patients, 182 were eligible for analysis. The median age was 60 years, and 54% were male. The Eastern Cooperative Oncology Group performance status was 0 (32%) or 1 (68%). The Royal Marsden Hospital (RMH) prognostic score was 0/1 in 59%. Single‐agent immunotherapy was given to 80% of the patients. Most patients (89%) received anti‐programmed death (ligand) 1 antibodies alone or in combination with other therapies. HPD occurred in 12 of 182 patients (7%). A higher proportion of females was seen among HPD patients ( P  = .01), but no association with age, performance status, tumor type, RMH prognostic score, combination immunotherapy, or CSAEs was found. The 1‐year overall survival rate was 28% for HPD patients and 53% for non‐HPD patients (hazard ratio, 1.7; 95% confidence interval, 0.9‐3.3; P  = .11). Conclusions: HPD was observed in 7% of patients with solid tumors treated with immunotherapy. HPD was not associated with CSAEs, age, tumor type, or the type of immunotherapy but was more common in females. Abstract : Hyperprogressive disease occurs in 7% of patients with mixed solid tumors treated with immunotherapy (predominantly anti–programmed death [ligand] 1 antibodies). Hyperprogressive disease is more common among females, but no association with other clinical factors or treatment‐related toxicity has been found.